Argumentation as a Collaborative Enterprise: A Study of Dialogic Purpose and Dialectical Relevance in Novice and Experienced Arguers - Felton, Mark; Crowell, Amanda (Informal Logic)

(untitled) (Informal Logic, 2022)
Studies of adolescents and young-adults suggest that deliberative dialogue, a form of consensus-seeking argumentation, leads to stronger learning outcomes than persuasive dialogue. However, this research has not been informed by an analysis of dialogue among more experienced arguers. In the present study, we compare the deliberative and persuasive dialogues of novice and experienced arguers to better understand the difference between these two forms of discourse at differing levels of argumentative expertise. Our results confirm theoretical distinctions between deliberation and persuasion. Results also suggest that greater experience in argumentation is associated with a richer array of argumentative purposes, producing more cohesive, intersubjective and dialectically relevant dialogue. The implications of these findings for learning are discussed.